Sofferenza, Cura E Relazioni Guarite Dall'Amore In San Francesco Di Assisi: Unzione e consolazione spirituale - Celestino, Francesco (Miscellanea francescana, 2024)
The life of St. Francis is marked in its various stages by illness and suffering. Biographers agree that he suffered from stomach, liver, spleen and eye pain. Francis had a special bond with every creature, re-establishing a brotherhood that finds its foundation in Jesus Christ. He urged the friars to take care of the sick as they would like it done for themselves when they are sick, both physically and spiritually. Two years before dying, he climbed the mountain of Verna and received the Sacred Stigmata as a sign of his love and passion for Christ. The "Poverello" (the poor man) strove to follow, imitate and conform his life to that of Christ. In our article we stopped to reflect on relationships healed by love, a sign of consolation and spiritual anointing in St. Francis.